Modified Mediterranean Diet for Enrichment of Short Chain Fatty Acids: Potential Adjunctive Therapeutic to Target Immune and Metabolic Dysfunction in Schizophrenia? - Joseph, Jamie; Depp, Colin; Shih, Pei-an B.; Cadenhead, Kristen S.; Schmid-Schönbein, Geert (Frontiers in Neuroscience, 2017)
Growing interest in gut and digestive processes and their potential link to brain and peripheral based inflammation or biobehavioral phenotypes has led to an increasing number of basic and translational scientific reports focused on the role of gut microbiota within the context of neuropsychiatric disorders. However, the effect of dietary modification on specific gut metabolites, in association with immune, metabolic, and psychopathological functioning in schizophrenia spectrum disorders has not been well characterized. The short chain fatty acids (SCFA) acetate, butyrate, and propionate, major metabolites derived from fermentation of dietary fibers by gut microbes, interact with multiple immune and metabolic pathways. The specific pathways that SCFA are thought to target, are dysregulated in cardiovascular disease, type II diabetes, and systemic inflammation. Most notably, these disorders are consistently linked to an attenuated lifespan in schizophrenia. Although unhealthy dietary intake patterns and increased prevalence of immune and metabolic dysfunction has been observed in people with schizophrenia; dietary interventions have not been well utilized to target immune or metabolic illness. Prior schizophrenia patient trials primarily focused on the effects of gluten free diets. Findings from these studies indicate that a diet avoiding gluten benefits a limited subset of patients, individuals with celiac disease or non-celiac gluten sensitivity. Therefore, alternative dietary and nutritional modifications such as high-fiber, Mediterranean style, diets that enrich the production of SCFA, while being associated with a minimal likelihood of adverse events, may improve immune and cardiovascular outcomes linked to premature mortality in schizophrenia. With a growing literature demonstrating that SCFA can cross the blood brain barrier and target key inflammatory and metabolic pathways, this article highlights enriching dietary intake for SCFA as a potential adjunctive therapy for people with schizophrenia.